A Wearable Vibrotactile Interface for Unfavorable Posture Awareness Warning - Lins, Christian; Fudickar, Sebastian; Gerka, Alexander; Hein, Andreas (in Proc. 4th International Conference on Information and Communication Technologies for Ageing Well and e-Health (ICT4AWE 2018), 2018)
We present the concept of a vibrotactile interface with up to 13 tactors (vibration motors) that are distributed over the full body to warn industry workers when taking unfavorable postures. The developed system is to be integrated into a motion capture workwear for industry workers to serve as posture feedback system to prevent unfavorable or even harmful postures. Such postures are a risk factor for musculoskeletal disorders (MSD), especially among older adults. We evaluated the vibrotactile system with 11 subjects to identify the optimal notification vibration sequences (regarding pulse length and repetition) and the accuracy of the location-dependent perception. Results indicate that the optimal pulse length is about 150 ms and is repeated 2 or 3 times within the sequence for maximum attention.
Keywords: Ergonomics Feedback; Haptics; Informationenfehlen; Occupational Ergonomics; Posture Warning; UNIAMT; UNILLM; Unpublished; Vibrotactile Interface; Wearables